Samizdatový bestseller - Petr Šámal (Česká Literatura)
This study examines the specifics of reading samizdat using Ludvík Vaculík’s novel A Czech Dreambook as an example. Following on from contemporary cultural-historical samizdat scholars (Ann Komaromi, Josephine von Zitzewitz and Jonathan Bolton), the author analyses various types of sources that testify to the reception of this novel. Another form of methodological inspiration here is the semiotic analysis of the act of publishing a work, presented by Miroslav Červenka. The author shows that Vaculík responded to samizdat’s limited publication opportunities by situating some of the readers in the immediate vicinity of the work and even involving these privileged readers in the constitution of the meaning of the novel.